Structural and durability assessment of ECC/concrete dual-layer system for tall wind turbine towers. (1st October 2019) - Jin, Qingxu; Li, Victor C.
Highlights: Iterative design method is developed to evaluate ECC/Concrete dual-layer system for tall wind turbine towers. ECC protective layers significantly prolong the service life of concrete wind turbine towers. ECC protective layers pose nonconsequential effects on the tower's structural performance. Abstract: The increasing consumption of wind energy necessitates the development of taller concrete turbines towers with larger installed rotors. A previous study demonstrated that a dual layer system that incorporates protective layers made from engineered cementitious composites (ECC) improves the durability performance of these towers (Jin and Li, 2019 [1] ). However, the introduction of ECC layers could affect the tower design due to its low elastic modulus relative to concrete. This paper first studies the structural impacts of the concrete towers with added ECC layers. An iterative method is employed to examine the requirements of strength, deflection, natural frequency and fatigue. The results show that ECC protective layer produces nonconsequential effects on tall concrete towers with less than 4% increase in tower diameter. After satisfying the aforementioned requirements, a durability analysis is conducted to compare the tower designs with and without ECC layers. The results indicate that the application of ECC layers significantly delays the initiation of chloride-induced corrosion of steel reinforcement and prolongs the service life of concrete wind turbine towers by four times. Therefore, this study allays the concerns that ECC protective layers may compromise the tower's structural performance and confirms its potential application in tall wind turbine towers for improved durability performance.